LIABILITY FOR DAMAGE IN IPHONE LEASING AGREEMENTS FROM THE PERSPECTIVE OF THE COMPILATION OF SHARIA ECONOMIC LAW: A CASE STUDY IN MEDAN JOHOR - Dea Livia; Sahliah Sahliah (Program Pascasarjana UIN Sumatera Utara, 2026)
This study examines liability for damage in iPhone rental practices in Medan Johor based on the Compilation of Sharia Economic Law (KHES). The phenomenon of iPhone rental is growing among young people, creative workers, and business people due to lifestyle and work needs. However, this practice often gives rise to disputes, especially when damage occurs to the rented item. This study aims to analyze the practice of iPhone rental in Medan Johor and examine the division of liability for damage to rented items based on the provisions of the KHES. The research method used is empirical juridical with a field study approach and literature review. Data were collected through interviews, observations, and documentation to obtain an empirical picture supported by normative analysis. The results show that according to the KHES, the lessee is responsible for damage caused by negligence, carelessness, or misuse, while damage arising from inherent defects, technical factors, or factors beyond the control of the lessee is the responsibility of the lessor. The case analysis shows differences in liability according to the cause of the damage, making it important for the parties to draft a detailed agreement. This research emphasizes the urgency of implementing the principles of justice, transparency, and good faith in ijarah contracts, especially for high-value modern electronic goods such as iPhones, so that legal certainty and protection for both parties can be guaranteed.